Maddoa: Tradisi Pesta Panen Masyarakat Di Desa Samaenre Kecamatan Mattiro Sompe Kabupaten Pinrang - Mrs. Rasnah; Mrs. Nurlela (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This study aims to find out the background of the maddoa' tradition in community harvest parties, examine how the dynamics of the maddoa' tradition in community harvest parties, and find out how the maddoa' tradition relates to the sustainability of people's livelihoods as farmers. The method used in this research is a qualitative method with a descriptive approach. Data collection techniques were obtained through observation, documentation and interviews involving several informants. The research results show the following: 1). Background The maddoa' tradition is a tradition that has been passed down from generation to generation which was originally held in 1956 as a form of gratitude to God for the harvest that was obtained as well as a form of togetherness and hospitality among residents in Samaenre Village, Pinrang Regency. 2). The dynamics in the Maddoa Tradition include the social changes that have taken place which have brought about changes in all aspects of life, the first time the implementation was not intense, the materials for the swing poles which were originally from areca tree trunks were adjusted to the available wood, the party tools were getting more and more modern. 3). We can see the relations that have been built between farmers until now by the cooperative attitude of the farmers who set aside their income so that the implementation of the maddoa tradition can be carried out properly and is a separate motivation for farmers to be more enthusiastic about carrying out their work.